2020
DOI: 10.1093/nutrit/nuaa119
|View full text |Cite
|
Sign up to set email alerts
|

The role of cultural beliefs on eating patterns and food practices among pregnant women: a systematic review

Abstract: Context Despite the importance of cultural beliefs in clinical practice, few systematic reviews have investigated how these beliefs influence food practices in pregnant women. Objective To explore the role of cultural beliefs in eating patterns and food practices among pregnant women, highlighting food recommendations, food taboos and restrictions, and their association with health. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…47 Finally, cultural beliefs, norms and social support given to a pregnant woman may affect her dietary patterns, macro-and micronutrient intakes, smoking, other health-related behaviours and health care utilisation, ultimately also affecting the duration of pregnancy and newborn size. [48][49][50] The most commonly highlighted adverse exposures that initiate or contribute to fetal growth restriction and preterm birth include maternal underweight 51 , short stature 52 , anaemia [53][54][55] , and infections. [56][57][58][59][60] Another large group includes various environmental exposures, such as air pollution [61][62][63] , intimate partner violence 64,65 , physical workload 66 , and tobacco 67 or alcohol 68,69 consumption.…”
Section: Conceptual Framework Of Svn: Multiple Causes Three Types Wid...mentioning
confidence: 99%
“…47 Finally, cultural beliefs, norms and social support given to a pregnant woman may affect her dietary patterns, macro-and micronutrient intakes, smoking, other health-related behaviours and health care utilisation, ultimately also affecting the duration of pregnancy and newborn size. [48][49][50] The most commonly highlighted adverse exposures that initiate or contribute to fetal growth restriction and preterm birth include maternal underweight 51 , short stature 52 , anaemia [53][54][55] , and infections. [56][57][58][59][60] Another large group includes various environmental exposures, such as air pollution [61][62][63] , intimate partner violence 64,65 , physical workload 66 , and tobacco 67 or alcohol 68,69 consumption.…”
Section: Conceptual Framework Of Svn: Multiple Causes Three Types Wid...mentioning
confidence: 99%
“…Some of these beliefs also prescribe the amount and type of food to be taken that will lead to safe delivery (Ekwochi et al 2016). African pregnant females adhere to their food beliefs and practices primarily as a form of respect and allegiance to their ancestors and for the safety of their babies (De Diego-Cordero et al 2020). Some of these beliefs are good, while others are injurious to the pregnant females and the development of the foetus.…”
Section: Food Beliefsmentioning
confidence: 99%
“…Findings from studies conducted in a range of LMICs, including Pakistan [ 2 ], South Africa [ 4 ], and India [ 6 ], show that the cultural food practices that pregnant women engage in can lead to restrictions of essential nutrients crucial for the health of both the mother and fetus. A recent review [ 7 ] of women in Kenya and Indonesia found they restricted food including meat, eggs, and fruit, during pregnancy as a way to avoid difficult deliveries and reduce the risk of caesarean sections [ 7 ]. However, it is worth noting that in some cultural contexts, there exists a belief that the avoidance or consumption of specific foods contributes to the health of both mothers and fetus [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%